Bacteriophage therapy: a possible alternative therapy against antibiotic-resistant strains of Klebsiella pneumoniae - Abbas, Sadia; Kanwar, Rabia; Ullah, Kaleem; Kanwal, Rimsha; Tajamal, Mamoon; Aslam, Muhammad Aamir; Ahmad, Abid; Qadeer, Abdul; Huang, Hsun-Yu; Chen, Chien-Chin (Frontiers in Microbiology, 2025)
Klebsiella pneumoniae is a notorious, Gram-negative pathogen and is a leading cause of healthcare settings and community-acquired infections. This is the commensal of human microbiota and can invade and cause infections in different body parts. The global emergence of antibiotic resistance in K. pneumoniae has become a major challenge in the whole medical community. Alternative paths to treat the infections caused by these MDR pathogens are needed as these bacteria become resistant to last-resort antibiotics like colistin. The lytic bacteriophages (phages) are the bacteria's natural predators and can rapidly eliminate the bacterial cells. Phages are abundant in nature and have recently been found to be effective tools in modern biotechnology. They can be used to control the bacterial infectious diseases. They can be manipulated easily and potentially used in therapeutics, biotechnology, and research. Several studies, both in vitro and in vivo, have demonstrated the possible applications of the lytic phages in treating K. pneumoniae superbug strains. Phage endolysins have drawn the scientific world's attention because of their involvement in phage adsorption and bacterial capsules digestion. These phage-encoded enzymes digest the polysaccharide components of bacterial cell walls by recognizing and binding them. Phage lysins, being strong biological agents, are capable of effectively and swiftly eliminating bacteria. This review summarizes the information on phages of K. pneumoniae and phage-based therapies to target their bacterial hosts.